Comparison of Regulations for Dissolution of Limited Partnerships in Indonesia and in America - Azizalia, Elsa Salsa (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
and dissolution mechanisms in the Indonesian limited partnership and the American limited partnership. The research used a normative legal method to examine inconsistencies between written norms and their application in court decisions. The findings showed that the Indonesian limited partnership imposed strict restrictions on limited partners, who were not permitted to engage in management activities, while the American limited partnership allowed limited partners certain managerial control through safe activities. The study also found that dissolution of the Indonesian limited partnership was not specifically regulated, causing reliance on general civil provisions, unlike the United States, which provided detailed rules for dissolution caused by breach of a partnership agreement. These results demonstrated significant differences in legal protection and dissolution mechanisms within both legal systems.